6-Chloro-N (4),N (4)-dimethylpyrimidine-2,4-diamine - Pang, Yuan-Yuan (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C(6)H(9)ClN(4), contains four independent molecules (A, B, C and D). Their main difference is the torsion angles, ranging from 1.6 (5) to 5.9 (5)°, between the methyl group and the pyrimidine plane. A pair of intermolecular N—H⋯N hydrogen bonds link molecules A and C into a twisted dimer with a dihedral angle of 32.9 (1)° between the two pyrimidine rings, creating an R (2) (2)(8) motif. In the packing, each two molecules of B, C and D form centrosymmetric dimers through two intermolecular N—H⋯N hydrogen bonds, locally creating R (2) (2)(8) motifs. The dimers of C and D are alternately bridged by A into an infinite zigzag strip, locally creating two different R (2) (2)(8) motifs with dihedral angles of 32.9 (1) and 63.4 (1)° between the pyrimidine rings. Finally, these strips together with the dimers of B associate into a complicated three-dimensional framework.